Feasibility, compressive strength and utilization of redmud in geopolymer concrete for sustainable constructions. (2021) - Jothilingam, M.; Preethi, V.
Abstract: The global demand for cement in the year 2050 is expected to be around 5.0 billion tons and the principal greenhouse gas, CO2 emission is projected to be around 4.0 Giga tons (from the cement industries), which contributes 5 percent of total global CO2 emissions and could cause adverse global warming and climate change. To reduce such effects and promote sustainable infrastructure development, an alternate to the Portland cement concrete is necessary. The manufacturing derivatives like fly ash (FA) of thermal power plants, red mud (RM) from alumina manufacturing industries, ground granulated blast furnace slag (GGBS) from steel industries, etc., are causing air pollution, ground water pollution, health hazard and occupy valuable land resource. The above mentioned industrial by-products, with addition of alkali activator solutions favour the manufacturing of geo-polymer concrete (alternate to Portland Cement concrete). This does not require water curing, and the rate of setting and hardening due to polymerization increases with ambient temperature. Thus water can be conserved and the strength is comparable with conventional concrete. In this experimental investigation, the M30 solid material with 50% fly ash and varying proportion of GGBS, red mud with activators made with alkali like Sodium silicate (Na2 SiO3 ) and Sodium Hydroxide (NaOH) solutions are used. The test on strength, durability properties, SEM and EDAX analysis of geo-polymer concrete were done to ascertain the suitability for construction activities.